Perkembangan Komunikasi Radio di Era Digital: Tinjauan Literatur yang Sistematis - Harlita Nindhasari; Harliantara Harliantara; Nurannafi FSM; Zulaikha Zulaikha; Didik Sugeng W. (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to comprehensively investigate the evolution and development of digital media in the context of broadcast radio communication. The main focus is directed toward the transition from analog radio broadcasting systems to digital and internet protocol (IP)-based platforms, which, while offering high efficiency, still present unique challenges for this century-old medium. The primary issue discussed is how the radio industry maintains its relevance, expands its reach, and monetizes content within an evolving and increasingly fragmented media landscape. By using a Systematic Literature Review (SLR) of 25 primary studies published in the past decade, this research explores shifts in audience consumption patterns, innovations in business models, and the ways technology is implemented. The results show that Media Convergence and Uses and Gratifications Theory are highly significant in understanding the radio adaptation process. Key strategies include utilizing podcasting as an on-demand strategy and integrating social media to enhance storytelling and transmedia communication. These conclusions indicate how radio broadcasting has transformed from a linear pathway into an interactive, multi-channel symphony. This study makes an important contribution to the academic world by exploring both the theoretical and practical aspects of radio communication in the context of convergence, while also offering valuable guidance for policymakers and media professionals.